HBR's 10 must reads on leadership (Havard Business Review Press, 2011)
If you read nothing else on leadership, read these 10 articles (featuring “What Makes an Effective Executive,” by Peter F. Drucker). We've combed through hundreds of Harvard Business Review articles on leadership and selected the most important ones to help you maximize your own and your organization's performance.